THE EFFECTIVENESS OF DIGITAL MULTILINGUAL THEMATIC DICTIONARY TO ENHANCE LITERACY OF FIFTH GRADE ELEMENTARY STUDENTS AT SDN 3 BANJAR JAWA - Sari Panjaitan, Polo Jumita; Ratminingsih, Ni Made; Santosa, Made Hery (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
This research aims to determine whether or not the digital multilingual thematic dictionary was effective to enhance the literacy skills of fifth grade students. This research method is quantitative-descriptive using the Classroom Action Research (CAR) technique The population consisted of class V students at SDN 3 Banjar Jawa. Students received treatments in every cycle. The instrument of this research is a student literacy test, which consisted of a pre-test, an observation sheet, and two post-tests. Data analysis was carried out using descriptive statistical analysis. This research is successful if the student's score above the minimum passing grade (KKM 70). The average score in the pre-test was 63.40, with 44% of students got the Minimum Mastery Criteria; in cycle 1, with an average score of 72.08, with a percentage of 72% of students got the Minimum Mastery Criteria; and in cycle 2, with an average score of 94.40, with a percentage of students who got the Minimum Mastery Criteria was 100%. This shows that the use of digital multilingual thematic dictionaries was effective to improve the literacy skill of fifth grade students.